The efficacy of trunk training treatment intensities on trunk control of stroke patients: a systematic review, meta-analysis and meta-regression - Nur-Akasyah J; Ridzwan MIZ; Razali MF; Mohd Ripin Z (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to assess the efficacy of trunk training treatment intensities on trunk control of stroke patients with the Trunk Impairment Scale (TIS) score. A structured literature search was performed in several databases from the first indexed article until December 2022, including PubMed, Web of Science, PEDro, Cochrane Library, and Scopus. In addition, the study selection was investigated following the PRISMA guideline. Only randomised controlled trials that examined the trunk training effectiveness on trunk control (measured by the TIS after stroke) were included. A total of 25 trials with 976 stroke patients were evaluated. Meanwhile, seven studies were classified as high bias risk. Irrespective of the training mode and methodology quality, the large effects favored trunk training compared to the control group. The sensitivity analysis revealed a large effect in favour of trunk training on trunk control [SMD = 1.16 (95% CI: 0.93-1.39); p<0.00001, I2 = 80%]. Subsequently, the most effective trunk training treatment duration was 10 hours of core stability exercise for trunk control improvement [SMD = 3.20 (95% CI: 2.25- 4.15)]. The meta-regression analysis demonstrated no strong evidence of trunk training treatment intensities on the effect sizes. Trunk training was effective in trunk rehabilitation. Nonetheless, specific trunk training was required for different stroke phases. Interestingly, the effect size was meaningfully enlarged by adding 15 minutes of core stability exercise to the conventional therapy (five sessions per week over eight weeks of intervention). This result was useful in determining the number of sessions for effective trunk rehabilitation